Provision of smoking cessation support in UK primary care: impact of the 2012 QOF revision. - Szatkowski, L; Aveyard, P (Royal College of General Practitioners, 2016)
Before 2012, UK GPs were paid only to offer cessation advice to smokers and only to those with smoking-related disease, a minority of all smokers. From 2012, GPs are now paid to offer all smokers referral for behavioural support and medication to assist cessation at least once every 2 years.To quantify the impact of this new recommendation and payment on indicators of smoking cessation activity.Interrupted time series analysis of data from general practices in England contributing data to The Health Improvement Network (THIN).Data were extracted on monthly rates of recorded delivery of smoking cessation advice, referral to NHS Stop Smoking Services, and prescription of smoking cessation medications, among an average of 3.3 million patients aged >16 years registered each month in THIN. ARIMA models were used to quantify changes in rates of cessation activity after the 2012 Quality and Outcomes Framework (QOF) revision compared with beforehand.The proportion of patients each month with a record of advice to quit smoking increased by 19.6% (95% CI = 7.9 to 31.4) in the year after the introduction of payments compared with the 8 years beforehand; the recording of referral to Stop Smoking Services increased by 38.8% (95% CI = 15.2 to 62.4). There was no significant change in prescription of smoking cessation medication, -7.7% (95% CI = -21.6 to 6.2).Paying GPs to intervene with all smokers and offer support rather than just advice to quit is associated with an increase in recording of advice and referring patients for behavioural support to stop smoking, but no change in prescribing pharmacotherapy for cessation.